PENGARUH ORIENTASI PEMBELAJARAN, KERJA CERDAS DAN KERJA KERAS TERHADAP KINERJA TENAGA PENJUALAN PERUSAHAAN FREIGHT FORWADING DI SEMARANG - Lisda Rahmasari (FEB Universitas Maritim Semarang, 2022)
This study aims to analyze the learning orientation on the performance of salespeople through smart work, and hard work owned by salespeople. High sales force performance is needed by the company so that sales success can be achieved. Learning orientation is one of the factors that have an influence on increasing salesperson performance, because with a learning orientation it can make a salesperson able to work smartly, have the ability to sell, so that the salesperson's performance will increase. The research method uses SEM (Structural Equation Modeling) analysis with the AMOS program. The results of the study prove that learning orientation, smart work and hard work have a positive influence on the performance of salespeople.